2022
DOI: 10.1155/2022/5034092
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtypes Based on Cuproptosis-Related Genes and Tumor Microenvironment Infiltration Characterization in Colorectal Cancer

Abstract: Recent studies have demonstrated the biological significance of cuproptosis modification, a newly discovered programmed cell death, in tumor progression. Nonetheless, the potential role of cuproptosis-related genes (CRGs) in the immune landscape and tumor microenvironment (TME) formation of colorectal cancer (CRC) remains unknown. We comprehensively assessed cuproptosis modification patterns of 1339 CRC samples based on 27 CRGs and systematically analyzed the correlation of these patterns with TME. The CRG-sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“… 10 , 41 It has been reported that m6A plays an increasingly important role in various physiological and pathological processes in various cancers, 42 including pancreatic cancer, 43 breast cancer, 44 and our published CRC study. 45 While the roles of various programmed cell death (PCD) modes in CRC prognosis have been explored in the literature, these models have primarily focused on individual modes of cell death, such as the apoptosis-related prognostic signature, 46 autophagy-related signature, 47 , 48 , 49 , 50 , 51 cuproptosis-related signature, 52 , 53 , 54 ferroptosis-related signature, 55 , 56 , 57 necroptosis-related signature, 58 , 59 and pyroptosis-related prognostic signature. 60 , 61 , 62 , 63 , 64 , 65 However, the interplay between m6A modification and PCD in CRC prognosis remains unexplored, representing a gap in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 41 It has been reported that m6A plays an increasingly important role in various physiological and pathological processes in various cancers, 42 including pancreatic cancer, 43 breast cancer, 44 and our published CRC study. 45 While the roles of various programmed cell death (PCD) modes in CRC prognosis have been explored in the literature, these models have primarily focused on individual modes of cell death, such as the apoptosis-related prognostic signature, 46 autophagy-related signature, 47 , 48 , 49 , 50 , 51 cuproptosis-related signature, 52 , 53 , 54 ferroptosis-related signature, 55 , 56 , 57 necroptosis-related signature, 58 , 59 and pyroptosis-related prognostic signature. 60 , 61 , 62 , 63 , 64 , 65 However, the interplay between m6A modification and PCD in CRC prognosis remains unexplored, representing a gap in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the large public database such as TCGA and GEO, we are able to access and analyze the transcriptome profiles of a variety of malignancies to gain a comprehensive understanding of genetic landscape, screen potential biomarkers, develop therapy strategies and predict patient outcome (68, 69). Several studies have described cuproptosis-related molecular patterns and the characterization of TME in colorectal cancer and found that cuproptosis patterns were closely associated with TME and served to predicted survival of patients with colorectal cancer (70)(71)(72)(73)(74). D. Hou, et al (75) developed a risk model of 11-cuproptosis-related lncRNAs to predict clinical and therapeutic implications of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients classified in the low‐risk group exhibiting stronger immunogenicity, higher immune scores, and a greater degree of microsatellite instability, suggesting a better response to immunotherapy. 50 , 145 , 155 , 156 , 157 , 158 , 159 Further investigation have highlighted the potential role of cuproptosis‐associated microRNAs and lncRNAs in CRC. For example, six cuproptosis‐associated miRNAs including hsa‐miR‐653, hsa‐miR‐216a, hsa‐miR‐3684, hsa‐miR‐4437, hsa‐miR‐641 and hsa‐miR‐552 were used to construct prognostic models.…”
Section: Role Of Copper and Cuproptosis In Crcmentioning
confidence: 99%
“…Moreover, cuproptosis is closely linked to the tumour immune microenvironment. Patients classified in the low‐risk group exhibiting stronger immunogenicity, higher immune scores, and a greater degree of microsatellite instability, suggesting a better response to immunotherapy 50,145,155–159 . Further investigation have highlighted the potential role of cuproptosis‐associated microRNAs and lncRNAs in CRC.…”
Section: Role Of Copper and Cuproptosis In Crcmentioning
confidence: 99%